Childhood sexual abuse as a potential predictor of psychotic like experiences in Tunisian college students. (May 2019) - Fekih-Romdhane, Feten; Tira, Salma; Cheour, Majda
Highlights: Higher rates of childhood trauma were reported across the spectrum of psychosis compared to the general population. Few studies have examined the link between Childhood Trauma and psychotic-like experiences (PLEs) in community samples. We found an association between a specific dimension of trauma, which is sexual abuse, and PLEs. Our results add support to the usefulness of probing previous sexual abuse during initial mental health screening. Abstract: Background: Current research has shown that experiencing childhood trauma may predispose individuals for psychosis and expression of Psychotic like experiences (PLEs). We aimed to examine the prevalence and characteristics of PLEs and depressive and negative experiences in a sample of Tunisian college students, and to evaluate the impact of childhood traumas in the occurrence and severity of these experiences at the time of the survey. Method: A total of 482 college students (63.7% female; aged 18–32) participated in a cross-sectional survey. The Positive Subscale of Community Assessment of Psychotic Experiences (CAPE) was used to measure PLEs. The Childhood Trauma Questionnaire was used to assess childhood trauma and neglect. Results: 53.5% ( n  = 258) of the students reported at least one positive PLE 'nearly always', and 40.9% ( n  = 197) reported at least one negative PLE with this frequency. After controlling for demographic variables (gender, age) and psychosocial factors (drug use, depression, anxiety and stress), sexual abuse significantly contributed to PLEs. Conclusion: There is a need for further cross-cultural research regarding the phenotypal expression of PLEs and its associated variables. Child sexual abuse victims should receive systematic and complete psychological screening during their adolescence/ early adulthood including, among others, PLEs and psychotic symptoms.